“iPSC-derived liver organoids and inherited bleeding disorders: Potential and future perspectives” - Roman, Giacomo; Stavik, Benedicte; Lauritzen, Knut H.; Sandset, Per Morten; Harrison, Sean P.; Sullivan, Gareth J.; Chollet, Maria Eugenia (Frontiers in Physiology, 2023)
The bleeding phenotype of hereditary coagulation disorders is caused by the low or undetectable activity of the proteins involved in hemostasis, due to a broad spectrum of genetic alterations. Most of the affected coagulation factors are produced in the liver. Therefore, two-dimensional (2D) cultures of primary human hepatocytes and recombinant overexpression of the factors in non-human cell lines have been primarily used to mimic disease pathogenesis and as a model for innovative therapeutic strategies. However, neither human nor animal cells fully represent the hepatocellular biology and do not harbor the exact genetic background of the patient. As a result, the inability of the current in vitro models in recapitulating the in vivo situation has limited the studies of these inherited coagulation disorders. Induced Pluripotent Stem Cell (iPSC) technology offers a possible solution to overcome these limitations by reprogramming patient somatic cells into an embryonic-like pluripotent state, thus giving the possibility of generating an unlimited number of liver cells needed for modeling or therapeutic purposes. By combining this potential and the recent advances in the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 technology, allows for the generation of autologous and gene corrected liver cells in the form of three-dimensional (3D) liver organoids. The organoids recapitulate cellular composition and organization of the liver, providing a more physiological model to study the biology of coagulation proteins and modeling hereditary coagulation disorders. This advanced methodology can pave the way for the development of cell-based therapeutic approaches to treat inherited coagulation disorders. In this review we will explore the use of liver organoids as a state-of-the-art methodology for modeling coagulation factors disorders and the possibilities of using organoid technology to treat disease